Karakteristik Bahan Bakar Biodiesel Minyak Jelantah Dengan Metode Partial Hydrogenation - Anugrah Raviery, Magfihza; Wirawan, I Ketut Gede; Ghurri, Ainul (Teknik Desain Mekanika, 2021)
Abstract Biodiesel is an alternative fuel derived from animal and vegetable raw materials. In other words, biodiesel is an environmentally friendly fuel, because the basic materials used include jelantah oil. However, jelantah oil cannot be immediately used directly as biodiesel, but rather must go through a process of esterification and transesterification such as by performing the Partial Hydrogenation method. This study aims to find out how the characteristics of biodiesel fuel jelantah oil with the Partial Hydrogenation method which includes viscosity, density, flash point, pour point, iodine number, and acid value. In this study using testing methods ASTM D445, ASTM D1298, ASTM D93, ASTM D97, SNI:7182, and ASTM D664. From the results of biodiesel testing that has been through the Partial Hydrogenation process, the quality of biodiesel produced meets the standard biodiesel quality requirements of the Indonesian National Standard (SNI) in 2015. Meanwhile, density and flash point do not meet the applicable biodiesel quality standards. This is because the test results of both characteristics are below the limit value. When compared to biodiesel oil without going through the Process of Partial Hydrogenation there is a decrease in the value at density, viscosity, flash point and pour point, as well as an increase in the value of acid content. Key words: Biodiesel, Characteristics, Jelantah Oil, Partial Hydrogenation